Respuesta :
Y=-2/3x+ 3 y=-1/6x-3 hope this helps if your finding slope. You subtract the x to the other side then divide the y
Answer:
(3, - 1 )
Step-by-step explanation:
Given the 2 equations
2x + 3y = 3 → (1)
x + 6y = - 3 → (2)
Multiplying (1) by - 2 and adding to (2) will eliminate the y- term
- 4x - 6y = - 6 → (3)
Add (2) and (3) term by term eliminating y
- 3x = - 9 ( divide both sides by - 3 )
x = 3
Substitute x = 3 into either of the 2 equations and solve for y
Substituting into (2)
3 + 6y = - 3 ( subtract 3 from both sides )
6y = - 6 ( divide both sides by 6 )
y = - 1
Solution is (3, - 1 )